Concerns arising from the calculation of the apnea-hypopnea index during CPAP-telemonitoring of patients with obstructive sleep apnea - Celia Vidal; Jean-Pierre Mallet; Sarah Skinner; Raphael Gilson; Olivier Gaubert; Arnaud Prigent; Frédéric Gagnadoux; Arnaud Bourdin; Nicolas Molinari; Dany Jaffuel (Respiratory Research)
Abstract Background Continuous Positive Airway Pressure (CPAP) telemonitoring is increasingly important in managing obstructive sleep apnea (OSA). The Apnea-Hypopnea Index reported by CPAP devices (AHIflow) is used as a key indicator of treatment effectiveness. However, discrepancies in AHIflow calculation rules between manufacturers may affect clinical decision-making. No prior studies have investigated whether manufacturers’ choices to exclude certain apnea-hypopnea events from the AHIflow calculation may influence the number of patients presenting an AHIflow alert. The aim of this proof-of-concept study was not to compare the manufacturers with each other, but to evaluate, for each manufacturer, how the different possible ways of calculating AHIflow influence the percentage of alert cases. Methods We conducted a retrospective analysis of 13,764 CPAP-treated OSA patients monitored on October 2, 2023. AHIflow calculations were evaluated according to manufacturer-specific rules. When possible, we assessed the impact of excluding central hypopneas, events during major leaks, and/or ramp periods on the percentage of patients crossing the consensual AHIflow alert threshold of ≥ 10 events/h. Results We identified significant disparities in AHIflow calculations between manufacturers, which lead to significant differences in the number of patients flagged as being in an alert state. Excluding central hypopneas reduced the number of alert cases by 50%, while excluding apneas/hypopneas during major leaks or ramp periods reduced alerts by 20%. Conclusions Our proof-of-concept study highlights inconsistencies in AHIflow calculations among CPAP manufacturers, raising concerns about patient care. Establishing standardized AHIflow calculation criteria is essential to ensuring accurate monitoring and optimal patient safety.